KOMPETENSI PROFESIONAL GURU PAI DALAM PEMBELAJARAN MEMOTIVASI DAN PEMBENTUKAN DISIPLIN SISWA MTS - Didit Darmawan; Muhammad Izzul Haq (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2026)
This study aims to analyze the professional competence of PAI teachers in managing motivating learning and shaping learning discipline of MTs students. Employing a qualitative literature review method with content analysis, this research synthesizes academic literature to develop a conceptual understanding of teacher competencies in both domains. The findings reveal that professional competence in managing motivating learning encompasses mastery of subject matter, understanding of adolescent characteristics, varied teaching methods, technology utilization, pleasant learning atmosphere creation, real-life relevance, intellectual challenges, constructive feedback, role modeling, positive personal relationships, understanding of motivation theories, continuous reflection, collaboration, comprehensive evaluation, and commitment to professional development. Professional competence in shaping learning discipline includes philosophical understanding of discipline, behavioral role modeling, value inculcation through PAI materials, structured routine habituation, clear rules and consequences, continuous monitoring and feedback, natural consequences utilization, positive classroom culture development, individual approaches, parental collaboration, persuasive approaches in handling violations, engaging learning creation, firmness with compassion, practice reflection and evaluation, and understanding discipline formation as part of Islamic education mission. The study implies that teacher professional development programs must comprehensively address all identified competence dimensions. Future research is recommended to conduct empirical studies testing the relationship between teacher competence and student motivation and discipline.